2003
DOI: 10.1074/jbc.m302238200
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Endothelial Nitric-oxide Synthase Autoregulates Cellular Activation and Pro-inflammatory Protein Expression

Abstract: Expression of inducible nitric-oxide (NO) synthase (iNOS) and "high-output" production of NO by macrophages mediates many cytotoxic actions of these immune cells. However, macrophages have also been shown to express a constitutive NOS isoform, the function of which remains obscure. Herein, bone marrowderived macrophages (BMDMØs) from wild-type and endothelial NOS (eNOS) knock-out (KO) mice have been used to assess the role of this constitutive NOS isoform in the regulation of macrophage activation. BMDMØs from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
115
2
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(129 citation statements)
references
References 58 publications
7
115
2
5
Order By: Relevance
“…The protective effect of upregulation of the low NO output NOS isoform, eNOS, by the NO donor during the hyperglycemic insult is supported by several studies in eNOS knockout mice, which revealed that this isoform serves cardioprotective and vasoprotective functions (Connelly et al, 2003;Gewaltig and Kojda, 2002;Jablonka-Shariff and Olson, 1998). These functions include modulation of vasoactivity and blood pressure, and inhibition of platelet aggregation, leukocyte adhesion and smooth muscle cell proliferation (Limbourg et al, 2002;Jugdutt, 2002;Papapetropoulos et al, 1999).…”
Section: Discussionmentioning
confidence: 78%
“…The protective effect of upregulation of the low NO output NOS isoform, eNOS, by the NO donor during the hyperglycemic insult is supported by several studies in eNOS knockout mice, which revealed that this isoform serves cardioprotective and vasoprotective functions (Connelly et al, 2003;Gewaltig and Kojda, 2002;Jablonka-Shariff and Olson, 1998). These functions include modulation of vasoactivity and blood pressure, and inhibition of platelet aggregation, leukocyte adhesion and smooth muscle cell proliferation (Limbourg et al, 2002;Jugdutt, 2002;Papapetropoulos et al, 1999).…”
Section: Discussionmentioning
confidence: 78%
“…1A). Expression of constitutive NOSs present in addition to iNOS and generating NO in the absence of inflammatory stimuli has been demonstrated in various cell types including rodent macrophages (22)(23)(24). However, in dendritic cells from both wild-type and iNOS Ϫ/Ϫ mice, endothelial nitric oxide synthase as well as neuronal nitric oxide synthase mRNA expression were close to the detection limit of ϳ5 ϫ 10 Ϫ9 mRNA copies per 18 S rRNA (data not shown).…”
Section: Effect Of Pteridines and L-nil On Dendritic Cellsmentioning
confidence: 97%
“…[17][18][19] Though TAMs have adopted a protumor phenotype, we and others have shown that they retain the potential to produce cytotoxic levels of inflammation, lyse surrounding cells, and coordinate an immune response from cells of the innate and adaptive immune system. [21][22][23][24] The ability to recapitulate these cytotoxic and immunostimulatory functions in TAMs, thus creating an antitumor phenotype, would be a powerful therapeutic tool for treating tumors and metastases with a significant macrophage population. An antitumor macrophage phenotype could potentially be produced by strategically manipulating the nuclear factor-kappaB (NF-κB) signaling pathway in TAMs.…”
Section: Introductionmentioning
confidence: 99%